Risk Factors For Unfavorable Outcomes After Bidirectional Cavopulmonary Anastomosis. (September 2017) - Nichay, Nataliya R.; Gorbatykh, Yuriy N.; Kornilov, Igor A.; Soynov, Ilya A.; Kulyabin, Yuriy Y.; Gorbatykh, Artem V.; Ivantsov, Sergey M.; Bogachev-Prokophiev, Alexander V.; Karaskov, Alexander M.
Background: Bidirectional cavopulmonary anastomosis (BCPA) is an important preliminary step toward the Fontan procedure; thus, understanding of risk factors for morbidity and mortality after BCPA may ultimately promote improved rates of success with Fontan completion and general survival. This study evaluated survival and predictors of unfavorable outcomes in patients after BCPA. Methods: Clinical data of 157 patients who underwent BCPA from 2003 to 2015 at a single center were retrospectively analyzed. Results: Three-year and nine-year survival after BCPA were 87.1% ± 2.8% and 85.8% ± 2.9%, respectively. Freedom from unfavorable outcomes (mortality, BCPA takedown, nonsuitability for Fontan procedure) was 83.8% ± 3.1% at three years and 73.5% ± 4.8% at nine years. Multivariate proportional hazards regression analysis revealed that total anomalous pulmonary venous connection (TAPVC; hazard ratio [HR]: 3.74, 95% confidence interval [CI]: 1.35-10.36; P = .01) and increased mean pressure in BCPA circuit (HR: 1.17, 95% CI: 1.02-1.34; P = .03) were independent risk factors for unfavorable outcomes. Postoperative mean pressure in BCPA circuit in patients with poor outcomes was median 16 mm Hg (interquartile range [IQR]: 14-18 mm Hg) versus median 14 mm Hg (IQR: 12-15.5 mm Hg) in patients with favorable outcomes ( P < .01). Preoperative (HR: 1.87, 95% CI: 1.20-2.91; P < .01) and postoperative atrioventricular valve regurgitation (AVVR; HR: 2.22, 95% CI: 1.24-3.94; P < .01) were also associated with unfavorable outcome in univariate Cox regression. Conclusions: Elevated mean pressure in the BCPA circuit is the main predictor of unfavorable outcome; therefore, thorough preoperative examination and careful patient selection are critical points for successful intermediate-stage and later Fontan completion. Total anomalous pulmonary venous connection and insufficient correction of AVVR worsen the prognosis in this patient group.